Airway immune response in the mouse models of obesity-related asthma - Kong, Jingwei; Yang, Fan; Bai, Minghua; Zong, Yuhan; Li, Zhuqing; Meng, Xianghe; Zhao, Xiaoshan; Wang, Ji (Frontiers in Physiology, 2022)
The prevalence rates of obesity and its complications have increased dramatically worldwide. Obesity can lead to low-grade chronic systemic inflammation, which predisposes individuals to an increased risk of morbidity and mortality. Although obesity has received considerable interest in recent years, the essential role of obesity in asthma development has not been explored. Asthma is a common chronic inflammatory airway disease caused by various environmental allergens. Obesity is a critical risk factor for asthma exacerbation due to systemic inflammation, and obesity-related asthma is listed as an asthma phenotype. A suitable model can contribute to the understanding of the in-depth mechanisms of obese asthma. However, stable models for simulating clinical phenotypes and the impact of modeling on immune response vary across studies. Given that inflammation is one of the central mechanisms in asthma pathogenesis, this review will discuss immune responses in the airways of obese asthmatic mice on the basis of diverse modeling protocols.